It's Not About "Freudian Couches and Personality Changing Drugs": An Investigation Into Men's Mental Health Help-Seeking Enablers. (November 2015) - Harding, Christine; Fox, Christopher
Enabling factors that influenced men to seek assistance for mental health concerns—a previous underresearched area—was the primary focus of this research. Past research spanning four decades has focused on men's barriers to mental health help-seeking with limited research positing social norms within men's peer groups and reciprocity as potential mental health help-seeking enablers. Using a qualitative design, nine men were interviewed to identify the positive factors they believed assisted their help-seeking decisions. Social norms, reciprocity, a significant other, and helpfulness of their general practitioner were domains identified in the analysis of participant narratives. The study revealed the participants' mental health and treatment illiteracy. Ignorance and misplaced stereotypes, initially acted as barriers to help-seeking, leading to denial of illness, impeding treatment, and perpetuating stigma. Sportsmen disclosing their mental health issues were identified as a positive influence for other men's help-seeking and assisted in the development of help-seeking as a social norm. The results of this study contribute to understanding the factors that enable men to seek mental health help.